Effect of sphingosine kinase 1 inhibition on blood pressure. Issue 2 (29th October 2012) - Furuya, Hideki; Wada, Masayuki; Shimizu, Yoshiko; Yamada, Paulette M.; Hannun, Yusuf A.; Obeid, Lina M.; Kawamori, Toshihiko
Abstract : Accumulating evidence suggests that sphingosine kinase 1 (SphK1) plays a key role in carcinogenesis by regulating cyclooxygenase‐2 (COX‐2) expression. Recent clinical studies have revealed that COX‐2 inhibitors cause adverse cardiovascular side effects, likely due to inhibition of prostacyclin (PGI2 ). In this work, we investigated the roles of SphK1 inhibition on blood pressure (BP). The results show that lack of SphK1 expression did not exacerbate angiotensin II (Ang II)‐induced acute hypertension, whereas celecoxib, a COX‐2 inhibitor, augmented and sustained higher BP in mice. Interestingly, SphK1‐knockout mice inhibited prostaglandin E2 (PGE2 ) but not PGI2 production in response to Ang II, whereas celecoxib blocked both PGE2 and PGI2 production. Mechanistically, SphK1 down‐regulation by siRNA in human umbilical vein endothelial cells decreased cytokine‐induced PGE2 production primarily through inhibition of microsomal PGE synthase‐1 (mPGES‐1), not COX‐2. SphK1 down‐regulation also decreased MKK6 expression, which phosphorylates and activates P38 MAPK, which, in turn, regulates early growth response‐1 (Egr‐1), a transcription factor of mPGES‐1. Together, these data indicate that SphK1 regulates PGE2 production by mPGES‐1 expression via the p38 MAPK pathway, independent of COX‐2 signaling, in endothelial cells, suggesting that SphK1 inhibition may be a promising strategy for cancer chemoprevention with lack of the adverse cardiovascular side effects associated with coxibs.—Furuya, H., Wada, M., Shimizu, Y., Yamada, P. M., Hannun, Y. A., Obeid, L. M., Kawamori, T. Effect of sphingosine kinase 1 inhibition on blood pressure. FASEB J. 27, 656–664 (2013). www.fasebj.org